Gambaran Jumlah Sel Monosit dan Sel Limfosit Pada Penderita Tuberkulosis Paru di UPTD Rumah Sakit Khusus Paru Provinsi Sumatera Utara - Sembiring, Terang U; Silfia, Marti; Erlan Aritonan; Denrison Purba (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2024)
Pulmonary TB is a chronic infection when associated with M.TB germs. Most mycobacterium tuberculosis germs infect the lungs, this triggers the cause of pulmonary tuberculosis, but these bacteria can infect other parts of the body. Transmission of tuberculosis can be caused by AFB Positive sufferers, AFB Negative sufferers and infections by inhaling air containing sputum microscopically. Tuberculosis is the main cause of monocytosis and lymphopenia. Monocytes are the body's immune response to detect tuberculosis in the form of cellular reactions and formation of the immune response is greatly influenced by the beginning. the body to tuberculosis in cellular reactions and as the main cells forming tubercles, monocytosis is an increase in the number above 900 / mm³. A decrease in the number of lymphocytes indicates an active tuberculosis process; Lymphocytes play an important role in the adaptive immune system against mycobacterium tuberculosis. A decrease in the number of lymphocytes is called lymphopenia below 2000/µL. The purpose of this study was to determine how many monocytes and lymphocytes were found in individuals suffering from pulmonary tuberculosis. Primary and secondary data were used to describe the study design. The laboratory examination method that uses this methodology is automatic, namely the Cell-dyn Emerald 22 hematology analyzer. From the results of the study at the UPTD Special Lung Hospital of North Sumatra Province, 20 samples examined contained 11 samples in a state of monocytosis (55%), 3 samples experienced monocytopenia (15%), and 6 samples with normal monocytes (30%). In lymphocytes there were 2 samples in a state of lymphocytosis (10%), 13 samples in a state of lymphopenia (65%) and 5 samples of normal lymphocytes (25%). An increase in monocytes indicates the activity of tubercle formation in the blood as a sign of active spread of tuberculosis and a decrease in lymphocytes indicates an increased risk of bacterial growth, and the body's ability to fight infection is hampered, resulting in permanent damage and causing lung complications.